Development Of Islamic Cultural History Teaching Materials In Improving Students' Learning Interest Through Youtube Media - Fakhry, Mochammad; Shohib, Muhammad (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2025)
In the era of rapidly developing information technology, the use of digital media in education is becoming increasingly important. Conventional teaching and learning no longer attracts students because it is boring, including in teaching and learning SKI. SKI material, which is related to Islamic history, requires a creative and related to Islamic history, requires a creative and innovative approach to keep students interested and motivated. innovative approach to keep students interested and motivated. The use of technological media such as YouTube is an effective solution. YouTube teaching and learning media can increase student interest and enthusiasm for learning, facilitate understanding of complex concepts, and provide easy access to educational content. complex concepts, and provide easy access to interesting educational content. educational content. This research aims to examine the potential and benefits of using the YouTube platform as a teaching and learning medium in the context of the history of Islamic culture. A qualitative descriptive method with a library research approach was used in this research. approach was used in this research. This research resulted in a statement that the use of YouTube media to Islamic Cultural History teaching materials has the potential to increase students' interest in learning students.